2005
DOI: 10.1111/j.1460-9592.2004.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of physical restraints on paediatric intensive care units

Abstract: Physical restraint is a commonly used technique on PICU in the UK. There is considerable variation in clinical practice and current clinical guidelines which are available do not deal specifically with children. Prospective randomized trials would be necessary to fully investigate the role of physical restraints amongst critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…; Graham and Hardy ; Homer and Bass ). Some studies also described devices which had been used to hold children or young people; these included splinting (Ofoegbu and Playfor ; Crellin et al. ; swaddling (Graham and Hardy ; Ofoegbu and Playfor ; Demir ), straps (Ofoegbu and Playfor ; Demir ) and commercial devices in radiological settings (Graham and Hardy ; Dashti et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Graham and Hardy ; Homer and Bass ). Some studies also described devices which had been used to hold children or young people; these included splinting (Ofoegbu and Playfor ; Crellin et al. ; swaddling (Graham and Hardy ; Ofoegbu and Playfor ; Demir ), straps (Ofoegbu and Playfor ; Demir ) and commercial devices in radiological settings (Graham and Hardy ; Dashti et al.…”
Section: Resultsmentioning
confidence: 99%
“…Physical restraints have been widely used in PICU to facilitate the tolerance of invasive monitoring and therapy and in an attempt to avoid treatment interference when the abrupt discontinuation of a treatment or intervention may lead to development of life-threatening complications (38). However, the role of physical restraints in preventing UE has not been prospectively studied (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of physical restraints in preventing UE has not been prospectively studied (38). Therefore, the main consensus in the adult literature is that the use of physical restraints has no scientific basis and that the benefits are unproven (39).…”
Section: Discussionmentioning
confidence: 99%
“…It may be concluded from the findings in this research that the rate of PR in Turkey was higher than those previously reported elsewhere. Ofoegbu & Playfor (2005) determined that 19 units used PR for patients; among these, 10 units used manual holding, 16 units used splints across limb joints, and three units used swaddling as a restraint technique in PICUs. Some PR applications were reported as follows: mechanical restraint rate 4–49% (Donovan et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been seen from the literature that the rate of informed consent from children was low. Ofoegbu & Playfor (2005) found that no written consent was obtained but verbal consent was obtained at the rate of 53% before PR in PICUs. Sifers et al.…”
Section: Discussionmentioning
confidence: 99%